Social workers and the neoliberal values of personal responsibility and self-sufficiency: Results of a NZ study - Renau D; Stanley-Clarke N; Mafile'o T (Oxford University Press on behalf of The British Association of Social Workers, 2026)
New Zealand society has entrenched neoliberal messaging of personal responsibility and self-sufficiency over the past forty years. This article addresses a gap in knowledge about social worker political ideologies in New Zealand. It reports on the findings of a quantitative survey administered to New Zealand social workers. The aim of the survey was to identify dominant political ideologies held by social workers, measure a range of socially authoritarian and right-wing economic attitudes, and identify if these attitudes are consistent with their self-identified political ideology. Following analysis using IBM SPSS Statistics software, the results of the study found that most respondents positioned themselves as Liberal or Progressive yet held more right-wing attitudes towards personal responsibility and self-sufficiency than their political ideology might have predicted. The most significant finding is social worker age made more of a contribution than political ideology with respect to attitudes and beliefs around personal responsibility and self-sufficiency. Social workers under the age of fifty are more likely than social workers fifty years or older to be unwittingly reflecting neoliberal values of personal responsibility and self-sufficiency onto their clients, which is then likely to further marginalize their clients.
Keywords: activism; age; neoliberalism; othering; political ideologies; social work identity